Investigation into interferometric sub-wavelength periodic feature fabrication and their applications - Sidharthan Raghuraman (2012)
Fabrication of sub-wavelength periodic structures requires advanced lithographic techniques so as to achieve uniform, large area patterns. Novel interference lithographic concepts/methodologies are proposed theoretically followed by experimental validation to fabricate uniform large area sub-wavelength periodic features. Further a multifaceted prism based zero path interferometer, for large area sub-micron patterning and immersion based interferometer for high resolution nano-scale patterning, is proposed and validated. Fabrication of complex features by interference lithography is one of the thrust research areas that were not fully researched. In this context, effect of the polarization states of individual beams in a multiple beam interference lithography was analyzed which led to the realization of a range of structures in 1D and 2D patterning. It is also found that body centered tetragonal, woodpile, β-tin type and diamond like structures can be obtained using multiple beam interference. Sub-wavelength periodic features are found to be very useful in various areas of nano photonics. Enhancing SPP propagation is explored using a periodic mask based near field lithography and with dye based gain medium. As one of the potential future applications, improving light absorption in thin film solar cell was also explored using the developed structures and proposed concepts.